2017
DOI: 10.1159/000479197
|View full text |Cite
|
Sign up to set email alerts
|

SGLT1 Deficiency Turns Listeria Infection into a Lethal Disease in Mice

Abstract: Background: Cellular glucose uptake may involve either non-concentrative glucose carriers of the GLUT family or Na+-coupled glucose-carrier SGLT1, which accumulates glucose against glucose gradients and may thus accomplish cellular glucose uptake even at dramatically decreased extracellular glucose concentrations. SGLT1 is not only expressed in epithelia but as well in tumour cells and immune cells. Immune cell functions strongly depend on their metabolism, therefore we hypothesized that deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Recently, tissue dual-transcriptome sequencing (RNA-seq) was applied to Y. pseudotuberculosis-infected mice and uncovered that Y. pseudotuberculosis increased expression of ptsG and other sugar transporter genes during infection (32). In addition, tissue dissected from the infected mice showed reduced expression of host glucose-specific transporters (33). In this context, the inability of the host to transport carbohydrates out of the lumen contributes to increased diarrheal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, tissue dual-transcriptome sequencing (RNA-seq) was applied to Y. pseudotuberculosis-infected mice and uncovered that Y. pseudotuberculosis increased expression of ptsG and other sugar transporter genes during infection (32). In addition, tissue dissected from the infected mice showed reduced expression of host glucose-specific transporters (33). In this context, the inability of the host to transport carbohydrates out of the lumen contributes to increased diarrheal disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested by recent literature, showing that absorption of SGLT1 inhibitors into the systemic circulation exerts its action on the heart, liver, lung, brain, and T‐lymphocytes, as well as the uterus, thereby possibly inducing serious side effects through localized SGLT1 inhibition. Moreover, SGLT1 inhibitors may compromise host defence against infection, as indicated by excessive bacterial loads in the liver, spleen, kidney and lung after Listeria monocytogenes infection, subsequently resulting in death of all SGLT1‐deficient mice . Because high postprandial plasma glucose concentrations have been linked to a strong predisposition to T2DM, any reduction in postprandial glucose surges should be beneficial for preventing or alleviating T2DM and its related complications .…”
Section: Discussionmentioning
confidence: 99%
“…inhibitors may compromise host defence against infection, as indicated by excessive bacterial loads in the liver, spleen, kidney and lung after Listeria monocytogenes infection, subsequently resulting in death of all SGLT1-deficient mice. 36 Because high postprandial plasma glucose concentrations have been linked to a strong predisposition to T2DM, any reduction in postprandial glucose surges should be beneficial for preventing or alleviating T2DM 37 and its related complications. 10 Hence, control of intestinal absorption of glucose with NHE3 blockade represents a promising therapeutic approach to moderating blood glucose levels, possibly with fewer side effects than previous intestinal SGLT1 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial glycogen, litter size, and pup weight were all lower in the Sglt1 -null mice than in wild-type mice. Similarly, in patients with RPL, the SGLT1 gene and protein expression were significantly lower during the implantation window as compared to control patients [76]. It was therefore concluded that SGLT1 deficiency in the human endometrium at implantation may predispose early pregnancy failure, obstetrical complications, and low fetal growth.…”
Section: Effects Of Sodium-glucose Transport Proteins On Recurrent Prmentioning
confidence: 99%